2016
DOI: 10.5483/bmbrep.2016.49.10.115
|View full text |Cite
|
Sign up to set email alerts
|

Mitophagy: a balance regulator of NLRP3 inflammasome activation

Abstract: The NLRP3 inflammasome is activated by a variety of external or host-derived stimuli and its activation initiates an inflammatory response through caspase-1 activation, resulting in inflammatory cytokine IL-1β maturation and secretion. The NLRP3 inflammasome activation is a kind of innate immune response, most likely mediated by myeloid cells acting as a host defense mechanism. However, if this activation is not properly regulated, excessive inflammation induced by overactivated NLRP3 inflammasome can be detri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
114
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(116 citation statements)
references
References 72 publications
(79 reference statements)
1
114
1
Order By: Relevance
“…Previous studies have reported that mitophagy negatively regulates inflammasome activation and metformin treatment decreases the expression of NLRP3, caspase‐1 and IL‐β in NDT2DM patients . However, our data appeared inconsistent with prior studies and revealed that metformin therapy led to augmented NLRP3 protein expression in these patients, which may subsequently trigger caspase‐1‐mediated pyroptosis of chronically activated macrophages, and thereby impeding chronic inflammation (Figure ).…”
Section: Discussioncontrasting
confidence: 94%
“…Previous studies have reported that mitophagy negatively regulates inflammasome activation and metformin treatment decreases the expression of NLRP3, caspase‐1 and IL‐β in NDT2DM patients . However, our data appeared inconsistent with prior studies and revealed that metformin therapy led to augmented NLRP3 protein expression in these patients, which may subsequently trigger caspase‐1‐mediated pyroptosis of chronically activated macrophages, and thereby impeding chronic inflammation (Figure ).…”
Section: Discussioncontrasting
confidence: 94%
“…Mitophagy, a mitochondria‐specific autophagy pathway, has been reported to be a negative regulator of NLRP3 inflammasome‐mediated hyperinflammation . Mounting evidence suggests that mitophagy and disruption of mitochondrial dynamics directly contribute to dopaminergic neuronal cell death in PD .…”
Section: Nlrp3 Inflammasome‐mediated Inflammatory Pathways In Pdmentioning
confidence: 99%
“…However, there is still a lack of drugs that directly interfere with NLRP3 inflammasome activation in clinical treatment. In addition, in LPS-primed macrophages, the interaction between endogenous ABRO1 and NLRP3 disappeared upon nigericin or ATP stimulation, implying that this key molecular mechanism of NLRP3 deubiquitination mediated by ABRO1 may contribute to the self-limiting regulation of inflammasome activation (Kim et al, 2016). Importantly, various DUBs are emerging as attractive therapeutic targets in diseases ranging from oncology to neurodegeneration, and firstgeneration DUB inhibitors are now approaching clinical trials (Harrigan et al, 2018).…”
Section: Of 17mentioning
confidence: 99%